Spatiotemporal characteristics, patterns, and causes of land-use changes in China since the late 1980s - Liu, Jiyuan; Kuang, Wenhui; Zhang, Zengxiang; Xu, Xinliang; Qin, Yuanwei; Ning, Jia; Zhou, Wancun; Zhang, Shuwen; Li, Rendong; Yan, Changzhen; Wu, Shixin; Shi, Xuezheng; et al. (Journal of geographical sciences, 2014)
Land-use/land-cover changes （LUCCs） have links to both human and nature inter- actions. China＇s Land-Use/cover Datasets （CLUDs） were updated regularly at 5-year inter- vals from the late 1980s to 2010, with standard procedures based on Landsat TM／ETM＋ im- ages. A land-use dynamic regionalization method was proposed to analyze major land-use conversions. The spatiotemporal characteristics, differences, and causes of land-use changes at a national scale were then examined. The main findings are summarized as fol- lows. Land-use changes （LUCs） across China indicated a significant variation in spatial and temporal characteristics in the last 20 years （1990-2010）. The area of cropland change de- creased in the south and increased in the north, but the total area remained almost un- changed. The reclaimed cropland was shifted from the northeast to the northwest. The built-up lands expanded rapidly, were mainly distributed in the east, and gradually spread out to central and western China. Woodland decreased first, and then increased, but desert area was the opposite. Grassland continued decreasing. Different spatial patterns of LUC in China were found between the late 20th century and the early 21st century. The original 13 LUC zones were replaced by 15 units with changes of boundaries in some zones. The main spatial characteristics of these changes included （1） an accelerated expansion of built-up land in the Huang-Huai-Hai region, the southeastern coastal areas, the midstream area of the Yangtze River, and the Sichuan Basin; （2） shifted land reclamation in the north from northeast China and eastern Inner Mongolia to the oasis agricultural areas in northwest China; （3） continuous transformation from rain-fed farmlands in northeast China to paddy fields; and （4） effective- ness of the ＂Grain for Green＂ project in the southern agricultural-pastoral ecotones of Inner Mongolia, the Loess Plateau, and southwestern mountainous areas. In the last two decades, although climate change in the north affected the change in cropland, policy regulation and economic driving forces were still the primary causes of LUC across China. During the first decade of the 21st century, the anthropogenic factors that drove variations in land-use pat- terns have shifted the emphasis from one-way land development to both development and conservation. The ＂dynamic regionalization method＂ was used to analyze changes in the spatial patterns of zoning boundaries, the internal characteristics of zones, and the growth and decrease of units. The results revealed ＂the pattern of the change process,＂ namely the process of LUC and regional differences in characteristics at different stages. The growth and decrease of zones during this dynamic LUC zoning, variations in unit boundaries, and the characteristics of change intensities between the former and latter decades were examined. The patterns of alternative transformation between the ＂pattern＂ and ＂process＂ of land use and the causes for changes in different types and different regions of land use were explored.